Negation in Nupe (2019)
Negation as a syntactic process has attracted tremendous attention cross linguistically. However. existing studies on the morpho-syntax of Nupe has concentrated on the study of the tense, aspect and the internal s t ru c tu re of th e verb phrase with little attention paid to negation. This study is, therefore, investigates negative constructions in Nupe with a view to identifying the negative markers and their distribution. as well as the scope of negation and its interaction with tense and aspect. Primary 'data were elicited using Ibadan Syntactic Paradigm, Focus Group Discussion and In-Depth-Interview while secondary data w e re collected from existing literature. The data were subjected to interlinear glossing and syntactic analysis. Two negative markers were identified: the negative particle a, and the negative circumfix ga-mɔ .. The negative particle a has the widest distribution and it is used in deriving various sentence types while ‘ga-m5’ is used only in negative imperatives. The negative marker a occurs sentence final in all instances of its occurrence. Using the syntactic and semantic processes of cleft focus and paraphrasing, the study distinguished between constituent and sentential negation. With regard to the interaction of tense/aspect and negation. It was observed that tense and aspect morphemes do not co-occur but either of them co-occurs with negative morphemes in the same construction. While the tense or aspect marker occurs pre-verbal, the negative morpheme occurs clause final.